EVALUASI KINERJA AUDITOR DALAM KETEPATAN PEMBERIAN OPINI AUDIT PADA KANTOR AKUNTAN PUBLIK - Rafida Bangki (Patria Artha Journal of Accounting dan Financial Reporting, 2019)
The problem in this study is how the auditor's performance in the accuracy of giving an audit opinion at the Public Accounting Firm and how internal control over the auditor's performance is in the accuracy of giving an audit opinion. This research has purpose: (1) to know and identify implementation of auditor performance in the accuracy of the provision audit opinion (2) identify and analyze the internal control on auditor performance in the accuracy of the provision audit opinion. This research used primary data through interviews of five  informant that worked in Public Accounting Firm (KAP) of Makassar and secondary data conducted through the collection of data relevant to the auditor performance in the accuracy of the provision audit opinion. Data acquired both primary data and secondary data, processed and analyzed using qualitative data analysis. The results of research shows that: (1) Auditor performance in the accuracy of the provision audit opinion of KAP is already adequate. It was discernible from the audit report that has been presented in accordance with attestation standards of financial as well and in implementing the examination must first define the audit work program and procedures the have been designed in the standard of field activity. (2) Internal control for the auditor performance of in the audit opinion in KAP has been optimum visible on the auditor's work is with the separation of duties and responsibilities in accordance with predetermined and has the honesty and thoroughness in implementing their respective duties of auditors and disciplinary obeyed by the auditor who has the authority in providing audit opinion on the financial statements of clients conducted by auditors working in KAP Makassar.